Professor Shlim Frankfurt and his «The Shrine of Solomon» – Mironivska Agricultural Experimental Station on culture and breeding of sugar beet (to the 150th anniversary of Solomon L. Frankfurt birthday) - V. A. Vergunov (History of science and technology, 2016)
The prerequisites for Mironivska (Central) Agricultural Experiment Station on culture and breeding of sugar beet are revealed in the context of the establishment and development of the Ukrainian sugar production and especially of the organization of its scientific support, and the place in these processes the prominent agrobiologist, one of the founders of experimental work and national academic science in Ukraine Professor Solomon L. Frankfurt.